Neuroprotectin D1 Protects Against Postoperative Delirium-Like Behavior in Aged Mice - Zhou, Ying; Wang, Jiayu; Li, Xiaofeng; Li, Ke; Chen, Lei; Zhang, Zongze; Peng, Mian (Frontiers in Aging Neuroscience, 2020)
Postoperative delirium (POD) is the most common postoperative complication affecting elderly patients, yet the underlying mechanism is elusive, and effective therapies are lacking. The neuroinflammation hypothesis for the pathogenesis of POD has recently emerged. Accumulating evidence is supporting the role of specialized proresolving lipid mediators (SPMs) in regulating inflammation. Neuroprotectin D1 (NPD1), a novel docosahexaenoic acid (DHA)-derived lipid mediator, has shown potent immunoresolvent and neuroprotective effects in several disease models associated with inflammation. Here, using a mouse model of POD, we investigated the role of NPD1 in postoperative cognitive impairment by assessing systemic inflammatory changes, the permeability of the blood–brain barrier (BBB), neuroinflammation, and behavior in aged mice at different time points. We report that a single dose of NPD1 prophylaxis decreased the expression of tumor necrosis factor alpha TNF-α and interleukin (IL)-6 and upregulated the expression of IL-10 in peripheral blood, the hippocampus, and the prefrontal cortex. Additionally, NPD1 limited the leakage of the BBB by increasing the expression of tight junction (TJ)-associated proteins such as ZO-1, claudin-5, and occludin. NPD1 also abolished the activation of microglia and astrocytes in the hippocampus and prefrontal cortex, which is associated with improved general and memory function after surgery. In addition, NPD1 treatment modulated the inflammatory cytokine expression profile and improved the expression of the M2 marker CD206 in lipopolysaccharide (LPS)-stimulated macrophages, which may partly explain the beneficial effects of NPD1 on inflammation. Collectively, these findings shed light on the proresolving activities of NPD1 in the pro-inflammatory milieu both in vivo and in vitro and may bring a novel therapeutic approach for POD.